2015
DOI: 10.1007/s10549-015-3408-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of adjuvant taxane-based chemotherapy on development of breast cancer-related lymphedema: results from a large prospective cohort

Abstract: Taxane-based chemotherapy for the treatment of breast cancer is associated with fluid retention in the extremities; however, its association with development of breast cancer-related lymphedema is unclear. We sought to determine if adjuvant taxane-based chemotherapy increased risk of lymphedema or mild swelling of the upper extremity. 1121 patients with unilateral breast cancer were prospectively screened for lymphedema with perometer measurements. Lymphedema was defined as a relative volume change (RVC) of ≥1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
73
2
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 64 publications
8
73
2
5
Order By: Relevance
“…These findings were also supported by Zhu et al [52] who also found a correlation between taxanebased adjuvant chemotherapy and the cumulative incidence of BCRL. Conversely, Swaroop et al [54] did not find any correlation between taxane-based chemotherapy and the development of BCRL, however there was some correlation between docetaxol to be a risk factor for mild swelling compared to no chemotherapy and non-taxane based chemotherapy. While there are new studies looking at neoadjuvant therapy as a risk factor for the development of BCRL, the findings are inconclusive.…”
Section: Incidence and Risk Factorsmentioning
confidence: 90%
“…These findings were also supported by Zhu et al [52] who also found a correlation between taxanebased adjuvant chemotherapy and the cumulative incidence of BCRL. Conversely, Swaroop et al [54] did not find any correlation between taxane-based chemotherapy and the development of BCRL, however there was some correlation between docetaxol to be a risk factor for mild swelling compared to no chemotherapy and non-taxane based chemotherapy. While there are new studies looking at neoadjuvant therapy as a risk factor for the development of BCRL, the findings are inconclusive.…”
Section: Incidence and Risk Factorsmentioning
confidence: 90%
“…Other studies have shown that age is not associated with BCRL (32,33). It was demonstrated that women treated with chemotherapy, specifically with taxane-based chemotherapy were more likely to develop lymphedema (34,35), but with inconsistent results (36). Extreme temperature and hypertension are risk factors for BCRL that have been confirmed in certain studies (37,38), however, further investigation is required.…”
Section: Risk Factorsmentioning
confidence: 99%
“…The incidence of cancer-related secondary lymphedema after lymph node dissection and/or sentinel lymph node biopsy can be as high as 63.4%, and this condition commonly results from treatments that include surgical intervention, radiation therapy, chemotherapy, hormonal therapy, and/or targeted therapy (174, 183). Notably, a prospective study with 1,121 patients showed that taxane-based therapy does not increase the risk of developing lymphedema (184). …”
Section: Impaired Lymphatic Function In Lymphedemamentioning
confidence: 99%